Early Occurrence of Two Distinct Histological Types of Renal Cell Carcinoma in End-Stage Renal Disease Patient on Haemodialysis - Parkhi, Mayur; Sekar, Aravind; Parmar, Kalpesh; Mandal, Shubajit (Annals of Pathology and Laboratory Medicine, 2020)
Background: The occurrence of renal cell carcinoma is a well-known complication in end-stage renal disease on haemodialysis. Various histological types of renal cell carcinomas are observed in these patients and varies with the duration of haemodialysis. Though the synchronous association of two renal cell carcinomas in the patients are known, the existence of such dual renal tumours in the patient on dialysis is extremely rare and unheard in the English literature. Moreover, tubulocystic renal cell carcinoma is rarely reported in this setting. Case report and Discussion: We describe an unusual early synchronous occurrence of two tumours with distinct histology i.e. Papillary renal cell carcinoma (PRCC, type I) and Tubulocystic renal cell carcinoma (TC-RCC) in a patient with end-stage renal disease on haemodialysis for a duration less than a year. Though exact etiological factors peculiar to the occurrence of these tumours are not known, increased oxidative stress occurring in end-stage renal disease patient on haemodialysis might play an important role in carcinogenesis. Conclusion: Renal cell carcinoma with more than one histological type may occur exceedingly early without any symptoms in these patients. Radiologists and urologists should be aware of it for early diagnosis and prompt treatment. Pathologists should also be more cautious while grossing and pick the sub-centimetric primary or secondary tumours that may have an impact on patient survival.